PENERAPAN MODEL DIRECT INSTRUCTION DENGAN METODE JARIMATIKA DALAM OPERASI HITUNG PERKALIAN PADA SISWA KELAS II SD N PALEBON 03 SEMARANG - Ayu Elviana, Nariska; Fita Asri Untari, Mei; Eka Subekti, Ervina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe and determine the effect of the Application of the Direct Instruction Model with the Jarimatika Method in Multiplication Arithmetic Operations on Grade II Students of Palebon 03 Elementary School, Semarang. This study uses a quantitative approach with a quasi-experimental research design in the form of a Nonequivalent Control Group Design. The subjects of this study consisted of an experimental class and a control class. The experimental class used the Direct Instruction model with the Jarimatika method, while the control class used conventional learning. Data collection techniques through tests (pretest and posttest). Data analysis includes normality tests, homogeneity tests, and hypothesis tests using t-tests or Welch's t-tests according to the swimmer test. The use of the Welch t-test was carried out because the data did not meet the assumption of homogeneity of variance. The results showed that there was no significant difference between student learning outcomes in the experimental class and the control class. This was indicated by a significance value of 0,101 > 0.05. However, the average posttest score of the experimental class tended to be higher than the control class. Thus, the application of the Direct Instruction model with the Jarimatika method has not provided a significant influence on the learning outcomes of multiplication operations in class II students of Palebon 03 Elementary School, Semarang.